Sistem Pendukung Keputusan Pemilihan Telur Menggunakan Metode Simple Additive Weighting (SAW) - Intan Pintaria Manalu; Darmansah Darmansah; Eko Bagus Prasetyo; Rahajeng Audi Nurianingrum (Journal of Information System Research (JOSH), 2022)
The development of laying hens, especially in Boyolali Regency, often experiences problems including the quality of the eggs produced by laying hens is not good, this can occur due to a number of factors such as physical composition (external) and the quality of the eggs themselves (internal). These factors can occur due to environmental factors, age, season, disease and feed. Therefore, this study was conducted to analyze the quality of laying hens using the simple additive weighting (SAW) method. The purpose of this study was to help laying hens breeders get good egg quality based on predetermined criteria, namely age, feed nutrition, chicken weight, chicken temperature, and vaccines. The techniques used to collect data in the research are interviews, observation and literature study. This study produces alternatives for each criterion and looks for the weight value of each attribute then a ranking process is carried out which will produce an optimal alternative to help chicken farmers in Boyolali district so that it is easier to get the best quality eggs produced by laying hens.